KAJIAN KEBUTUHAN ANGKUTAN LAYANAN PERGERAKAN INTERNAL KAMPUS INSTITUT TEKNOLOGI SUMATERA - Siti Rahma; Goldie Melinda Wijayanti; Zenia F Saraswati (FROPIL (Forum Profesional Teknik Sipil), 2021)
Besides of the lecture buildings and laboratories facilities, transportation modes are also needed to facilitate academicians’ movement needs. Institut Teknologi Sumatera (ITERA) is the first public technology institution on Sumatra, which is located on the border of South Lampung regencies and Bandar Lampung City. From the survey results, it is known that 27% of the academic community, consisting of lecturers, education staff, and students, do not own private vehicles. It caused an accessibility problem, which is the absence of public transportation that serves internal movements for the captive group. In campus internal service transportation’s planning, there are several analyzes will be carried out to find out how important the internal movement facilities in the ITERA campus area, and the types of vehicles that can serve the movement requests that occur. Based on the survey results, it is known that the internal campus movements are carried out by all ITERA academicians, with the peak transfer hour at 15.00-16.00 WIB. From the analysis of the existing geometric conditions, it can be seen that the lane width on the ITERA internal ring road is more than 2.5 m, which means that it is sufficient to serve the movement Light Vehicles (LV) and medium or large buses according to the type classification. land public transport vehicles. In addition, from the choice group, more than 50% of respondents stated that they are willing to use public transportation that serves the internal movements of the ITERA campus if these facilities are already available.